Estudo comparativo das anomalias dentárias em crianças portadoras e não portadoras da síndrome de Down - Ramos, Ingrid Tigre (2017)
Introduction: The awareness of the dental characteristics associated with Down syndrome (DS) is fundamental to improve the quality of the dental service offered to these patients. Objective: Verify the types of systemic alterations present in children with DS; to investigate dental and jaw abnormalities, and the dental maturation stage in these children, comparing the results with a group of nonsyndromic children. Material and methods: The sample consisted of 93 panoramic radiographic exams, of which 31 were children with DS, who constituted the experimental group (EG), and 62 non-syndromic children that composed the control group (CG), aged 6-12 years. The variables studied were: systemic alterations (hypothyroidism, heart disease, alterations in airways, others), being evaluated only in the EG; dental anomalies (presence, absence, type and location), jaw abnormalities (presence, absence, type and location) and dental maturation stage, according to the Demirjian’s method. To verify the association of the variables, the chi-square statistical test was performed, considering values of p<0.05. Results: Out of the study population, 74% (n=23) of the EG presented some kind of systemic alteration (p<0.0001), being the most commonly found alterations in airways (45%; n=14). Dental anomalies were present in 74% (n=23) cases in EG and in 24% (n=16) in CG (p<0.0001), with a higher prevalence in EG for: hypodontia (p<0.0001), taurodontism (p=0.002) and microdontia (p=0.002). In EG, 69,6% (n=16) of dental anomalies were located in maxilla and mandible simultaneously (p <0.0001) and 65% (n=15) concomitantly in anterior and posterior regions (p=0.003). No jaw abnormalities were observed in EG, and in CG were observed in 6 (9%) patients (p=0.17). There was no statistically significant difference in the maturation stage between the groups. Conclusion: DS children have a high incidence of systemic alterations and, when compared to non-syndromic children, have a greater number of dental anomalies.